The Determinants of Online Vegetables/Fruits Repurchase Intention: Stimulus-Organism-Response Model and Theory of Planned Behaviour - Fikri, Amir; Nurmalina, Rita; Najib, Mukhamad; Simanjuntak, Megawati (European Scientific Journal, ESJ, 2019)
The aim of this study is to review of concepts, theories and models related to consumer intentions. In doing this, the objective is to explore and explain the determinants of online vegetables/fruits repurchase intention based on literature review which used Stimulus-Organism-Response (SOR) Model and Theory of Planned Behaviour as basic concepts approach to put forward hypotheses for next research on consumer intention. Many research in the past examined variables as antecedents and predictors of repurchase intention. This literature study refers to the repurchase intention framework with a content of reputation, emotion, perceived risk, subjective norms, attitude, and perceived behavior control. The authors explore variables on these concepts, data for this study were generated through secondary data from many sources including paper, journal, textbooks, databases, and websites, etc. The literature review found that there is a positive relationship between reputation and emotion towards online repurchase intention, and perceived risk give a negative influence to online repurchase intention. The reputation of e-retailers is very important as it has a positive impact on online repurchase intention of e-shoppers in the future. Subjective norms have a direct significant impact on buying intentions. Subjective norms influence attitudes toward buying intentions. That attitudes and perceived behavior control are better predictors of intentions when the social environment is more conducive and supportive to perform a behavior. The present study found that perceived behavioral control significantly influences willingness to online repurchase intention toward fresh vegetables or fruits. Hence, the study provides the summary of existing literature related to repurchase intention for better understanding and helps to frame the hypothesis for future research. While some outcomes may be significant to marketing practice, the overall goal of such research is to achieve a better understanding of consumer behavior.